Facial Plexiform neurofibromatosis in a patient with neurofibromatosis type1: a case report - Iffat Hassan; Abid Keen; Parvaiz A. Shah (Our Dermatology Online, 2012)
Plexiform neurofibroma is a poorly circumscribed, diffuse enlargement of neural sheets that typically involves major nerve trunks of the head and neck region because of the rich innervations of this area. It is a benign tumor and is a virtually pathognomonic and often disabling feature of neurofibromatosis type 1 (NF-1 or Von Recklinghausen's disease). We hereby report a case of facial neurofibroma in an adult female with neurofibromatosis type 1 (NF-1).